Age at Immigration and High School Dropouts - Sarit Cohen Goldner; Gil S. Epstein (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
We focus on high school dropout rate among male and female immigrant children. We consider the relationship between the dropout rate and age of arrival of the immigrants. Using repeated cross sectional data from the Israeli Labor Force Surveys of 1996-2011 we show that the share of high school dropouts among immigrant children who arrived from the Former Soviet Union during 1989-1994 is at least as double than among natives in the same age group. Further, we show that among immigrant youth there is a monotonic negative relation between age at arrival and the share of high school dropouts. To understand our results we present a theoretical framework that links between age at arrival in the host country, language proficiency, quality of education and wages.
Keywords: I21; J24; J61; 330; Immigrants; age at arrival; high-school dropouts